ANALISIS YURIDIS ATAS PERAN NOTARIS TERHADAP PENYELESAIAN SENGKETA DENGAN PERDAMAIAN - MUHAMMAD TAUFIK ATMA (PREMISE LAW JURNAL, 2016)
A peace treaty as the result of a process of dispute settlement should be in a written form in order to prevent from the reemergence of the same dispute in the future. Therefore, the process can be done outside of the court by making a deed, a peace treaty which can be underhanded or authentic made by a Notary. A Notary has to provide legal counseling and can answer any questions asked by his clients. He must not give wrong explanation which violates the law. His role in making peace treaty is to make authentic deed as stipulated in Article 16 of UUJN and to formulate the willingness and action of the persons appearing into the authentic deed. He also has to attach the register number of the Court in the peace treaty made before him. He is not liable for the content of the deed made before him; he is only responsible for its formal form according to legal provisions. Keywords: Notary, Reconciliation Deed, Dispute Settlement